APLIKASI SISTEM CERDAS GUNA MENDUKUNG DAN MEMPERCEPAT PROSES PEMILIHAN KEPALA DESA ELEKTORONIK MODERN PEMILU (EMPEMILU) STUDI KASUS DI DESA BEJI KECAMATAN KEDUNG BANTENG KAB. BANYUMAS - Azis, Abdul; Tarwoto, Tarwoto (Aksara Public, 2019)
The election of the Village Head was very directly highlighted by the surrounding community, from the way of employment, budget use and so on. Pilkades in each region, especially in the Village of Beji Banyumas, will be held by a choice of the Village Head for choices in 2019 after the presidential election is held. The general election of the Village Head in Beji still uses the same paper as the general election, this makes a waste of budget because the unused paper will be discarded, the unused rooms will be kept for 5 years, the calculation of the election results is not fast enough. The Election Smart System is the solution where the workings of this System are done using sophisticated computers, including the Touch Screen Screen used to select Candidate Images, Face detection cameras are used for attendance attendance if it is going to the selection booth, DasHboard Diagrams are used to see the results of prospective candidates the winner will be directly displayed on the big screen to be seen by all those who want to know the most votes from the candidates, all the above facilities are run by computers, so there is no interference from the KPU or individuals who will misuse prospective voter data.